Presiden Non-Muslim dalam Komunitas Masyarakat Muslim - Mary Silvita (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2012)
This paper examines the notion of state and leadership according to the contemporary Islamic thought. To be more precise, the paper asks whether it is possible for a non-Muslim to be the president of the majority Muslim country. To answer this, the paper will dwell into the problem of citizenship both in classical and modern Islamic thought by taking into account the political and social situation that shapes this thought. The paper maintains that many Muslims?both in the past and at the present?fail to offer a proper discourse on statehood and leadership in Islamic perspective. The mainstream discourse on this issue?the paper argues?is that which keeps in a good balance the notion of religiosity and citizenship. The rightwing Muslims will provide a textual understanding of the problem, while the left-wing will otherwise offer a secular interpretation of it. This paper will try to keep the two in a balance, and present a fair understanding of what the Qur'an and the Sunnah say about the problem at hand.